2018
DOI: 10.1017/s1368980018003117
|View full text |Cite
|
Sign up to set email alerts
|

Mobile app increases vegetable-based preparations by low-income household cooks: a randomized controlled trial

Abstract: ObjectiveWe built an app to help clients of food pantries. The app offers vegetable-based recipes, food tips and no-cost strategies for making mealtimes healthier and for bargain-conscious grocery shopping, among other themes. Users customize materials to meet their own preferences. The app, available in English and Spanish, has been tested in a randomized field trial.DesignA randomized controlled trial with repeated measures across 10 weeks.SettingClients of fifteen community food pantry distributions in Los … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 26 publications
0
33
0
Order By: Relevance
“…Since over 77 % of Americans own a smartphone and 64 % of smartphone users live in households earning less than $US 30 000 per year, there is potential for broad reach of mobile health (mHealth) technology, which includes using mobile and wireless devices to improve health outcomes among lower-income populations (19) . Emerging research has suggested that mobile apps may be an effective approach to supporting healthier food purchasing behaviours (20) , healthier food preparation methods (21) , and healthier recipe management and meal planning behaviours (22) , but that there is a need to engage mobile app users and nutrition professionals in the design.…”
mentioning
confidence: 99%
“…Since over 77 % of Americans own a smartphone and 64 % of smartphone users live in households earning less than $US 30 000 per year, there is potential for broad reach of mobile health (mHealth) technology, which includes using mobile and wireless devices to improve health outcomes among lower-income populations (19) . Emerging research has suggested that mobile apps may be an effective approach to supporting healthier food purchasing behaviours (20) , healthier food preparation methods (21) , and healthier recipe management and meal planning behaviours (22) , but that there is a need to engage mobile app users and nutrition professionals in the design.…”
mentioning
confidence: 99%
“…Perhaps the advantage from printed output was due to the reasons that led us at the outset to build the app to provide tangible VeggieBooks and SecretsBooks. Many household cooks, one-third in our RCT experiment testing app effectiveness (Clarke et al 2019), preferred using printed recipes compared with the recipes on the phone, a device that can get wet and greasy in the kitchen. Also, in households with just one smartphone, many cooks cannot commandeer the device during times of value to them, such as visiting food pantries, preparing meals, or shopping.…”
Section: Resultsmentioning
confidence: 99%
“…We tested the app's effectiveness in a randomized controlled trial with nearly 300 households. Briefly, app-enabled household cooks began preparing 38% more vegetable-based servings than the control group, and showed other and sustained signs of healthier food use across a 10-week study period (Clarke et al 2019).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations